Framing BPJS Kesehatan Crisis Narratives on Tiktok - Sekar Arum Nuswantari; Noveria Anggraeni Fiaji (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2026)
This study examines how the Indonesian Social Security Agency for Health, Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS Kesehatan) and selected online media posts framed public trust-related controversies on TikTok. A qualitative method and a framing analysis approach used to examine BPJS Kesehatan posts‚ as well as selected online news media posts that frame conflicts regarding public trust on TikTok․ The selected posts are thirteen TikTok posts published from 1 January 2022 to 31 May 2025‚ consisting of seven posts by the BPJS Kesehatan account and six from online news media accounts․ The captions, spoken transcriptions, and on-screen texts were coded using Entman’s four framing functions and subsequently interpreted through Hallahan’s framing framework and Situational Crisis Communication Theory (SCCT). The analysis results show that BPJS Kesehatan's framing strategy is relatively consistent in the clarification-and-reassurance dimension‚ through correction of misinformation‚ explaining the procedure‚ the justification‚ and reassurance of the institution․ The content of the media posts that were selected was more mixed‚ with some reproducing institutional clarification‚ providing explanations of policy changes‚ describing governance gaps from within claims‚ criticizing reporting by the government‚ and representing fraudulent actions by healthcare services․ Framing alignment and framing divergence were also obvious․ Attributing blame to different actors‚ BPJS reacted more strongly to misinformation- and procedure-related frames than to governance‚ accountability and provider malfeasance frames.